THE GERM THEORY OF DISEASE AND ITS RELATIONS TO HYGIENE - Barnard, Frederick Augustus Porter (Hygeia - Revista Brasileira de Geografia Médica e da Saúde, 2012)
No more striking evidence can be adduced of the intellectual advancement characteristic of modern times, than the general recognition among men of the universal reign of law. It is true that this general recognition has not yet become quite universal. There are not wanting many, even in our enlightened age, to whom the advent of a comet still brings feelings of dismay, and in whose belief the wind literally bloweth where it listeth, every day. The belief in lucky and unlucky days has by no means disappeared, and among even the well educated there are yet some who would not willingly put to sea on the brightest Friday morning that ever shone. It is difficult to disabuse the mind of impressions which almost inevitably find a place there in the infancy of individuals and of peoples. Every event of which the causes are obscure, is naturally attributed by the ignorant or inexperienced, either to blind chance or to the purposed interference of some supernatural power; and such is the strength of the imagination that the feeling often survives long after reason has exploded the error.